2019
DOI: 10.1038/s41371-019-0274-z
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and validation of spot urine in estimating the 24-h urinary sodium, potassium, and sodium/potassium ratio in Chinese adults

Abstract: The commonly used methods of estimating the 24-h urinary sodium (UNa) and urinary potassium (UK) from spot urine (SU) are the Kawasaki method (K-method), INTERSALT method (I-method), and Tanaka method (T-method), but the method that is suitable for use in the general Chinese population is still uncertain. We aimed to assess and validate these methods in estimating the 24-h UNa and UK using SU samples in Chinese adults. We studied 1428 individuals aged 18-69 years using SU and 24-h urine samples. For the K-meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 37 publications
4
23
2
Order By: Relevance
“…Two previous studies reported that Tanaka performed well to predict mean population 24-hUNa excretion in both Chinese adults [16] and young adolescents [17], which was in conformance with our study. Nevertheless, other previous studies in Chinese adults found that the Kawasaki formula showed the lowest bias compared to Tanaka and INTERSALT formulas in both general [18][19][20][21] and hypertensive populations [22]. However, the Kawasaki formula performed worst among the six equations in our study.…”
Section: Discussioncontrasting
confidence: 79%
“…Two previous studies reported that Tanaka performed well to predict mean population 24-hUNa excretion in both Chinese adults [16] and young adolescents [17], which was in conformance with our study. Nevertheless, other previous studies in Chinese adults found that the Kawasaki formula showed the lowest bias compared to Tanaka and INTERSALT formulas in both general [18][19][20][21] and hypertensive populations [22]. However, the Kawasaki formula performed worst among the six equations in our study.…”
Section: Discussioncontrasting
confidence: 79%
“…and ICCs of 0.31 and 0.27 (all P < 0.01), respectively, while the mean bias for the Kawasaki method in estimating 24UKV was the least among these methods (16) . In the subgroup analysis regarding different gender and timing of spot urine, all other mean absolute difference between estimated and measured values were all significant different, except for those from Tanaka formula using morning, afternoon, and evening spot urine.…”
Section: Discussionmentioning
confidence: 83%
“… 23 , 24 , 25 , 26 For example, Peng and colleagues studied rural and urban residents from Shanxi Province who were participating in the Prospective Urban Rural Epidemiology (PURE)‐China study, and found that the mean differences between the measured values and values estimated using the Kawasaki, Tanaka, and INTERSALT methods were −740.49, −2305.05, and −2797.39 mg/day. 24 Other studies 23 , 25 , 26 that were performed in the Chinese populations also demonstrated that the differences between the measured values and values estimated using the Kawasaki method were smaller than that those obtained when using the Tanaka or INTERSALT methods. In addition, a sub‐study of the PURE study, which was of 1083 participants aged 35–70 years who were recruited worldwide, obtained similar results.…”
Section: Discussionmentioning
confidence: 99%